G458(P) UK Paediatric Intensive Care units overestimate central venous catheter fill volumes. Fill volumes are proportional to trimmed central venous catheter length. (7th April 2014) - Green, P; Keene, DJB; Melville, S; Minford, J
Abstract : Aims: 200, 000 central venous catheters (CVCs) are inserted annually in the NHS. CVCs are regularly flushed before and after use, and also "locked" with anticoagulants or antibiotics. Manufacturers publish fill volumes for full-length CVCs however tunnelled CVCs are routinely trimmed at the time of insertion so this data may not be accurate. This study aims to: Calculate the fill volumes of commonly used CVCs when trimmed. Investigate current fill volumes used in Tertiary Paediatric Intensive Care Units in the UK Assess the length of CVC trimmed at the time of insertion. Methods: Single lumen (SL) (2.7F, 4.2F, 6.6F and 9.6F), and double lumen (DL) (7F and 9F) Broviac ® CVCs were assessed. Each CVC was connected to a MicroClave ® connector and saline was instilled at 0.2 ml/second until saline droplet was seen to emerge from the tip. The CVC was then trimmed by 5 cm and the experiment repeated. 3 repeat measurements were obtained and catheters were fully flushed with air between readings. A telephone survey of tertiary Paediatrics Intensive Care units (PICUs) in England was performed in September 2013. Recommended CVC lock volumes were recorded. A prospective audit of trimmed CVC lengths was performed at the time of insertion. Results: The MicroClave ® connector adds 0.04 mls to the fill volume of a CVC. Trimming the CVC to its minimum length can reduce the fill volume by 50% compared to the manufacturer's data. The correlation between total CVC length and fill volume is a linear one, allowing CVC fill volumes to be accurately estimated (Fig 1 ). The median volume of CVC flush used in PICUs across the UK is 5 mls (Range 1.5–20 mls) (Fig 2 ). The median proportion of a CVC trimmed at the time of line insertion is 59% (Range 16–61%). Conclusions: Trimming a CVC dramatically reduces the fill volume. Majority of UK Paediatric Intensive Care units overestimate central venous catheter fill volumes with consequences of potential fluid overload. Recording total CVC length at insertion can enable accurate estimation of CVC fill volumes.